Efeitos do treinamento físico aeróbico sobre a reatividade vascular em anéis de aorta de ratas ovariectomizadas e infartadas - Oliveira, Suelen Guedes de (2017)
The main characteristic of women in the postmenopausal period is the ovarian hormones deficiency. It is known that it is the time when the woman is most susceptible to the incidence of cardiovascular diseases. Among the CVDs that most affect women during their lifetime, the acute myocardial infarction (AMI) is highly significant. In order to reduce hospitalization rates and population mortality, aerobic training may be an important therapeutic strategy aimed to reduce the side effects of disease and improving the patients' quality of life. Therefore, the aim of the present study was to evaluate the effects of exercise training on vascular reactivity in aorta rings of ovariectomized and infarcted rats, from a perspective of the antioxidant system. The animals were submitted to ovariectomy 7 days after induction of AMI or fictitious surgery. Then, the animals were divided into sedentary or trained groups, who started the training 15 days after AMI and performed the training for 8 weeks, resulting in the following groups: Control, OVX+SHAMsed, OVX+SHAMef, OVX+IMsed and OVX+IMef. After the exercise training period, animals were sacrificed and the vascular reactivity was assessed in aorta rings. Investigation of antioxidants protein expression and of gp91phox was made by the western blotting method and the superoxide anion production was evaluated by the dihydroethidium fluorescence (DHE). After AMI there was an increase in vessel contractility and an impairment in the endothelium-mediated relaxation. On the other hand, the group submitted to exercise training showed a higher relaxation compared with the sedentary infarcted rats, in addition to a lower contraction. Moreover, the protein expression of the pro-oxidant protein gp91phox and the superoxide production was higher in the OVX+IMsed group compared to OVX+Shamsed. In infarcted rats, exercise training was able to prevent these changes. The present study highlights the importance of exercise training as a therapy which helps to provide a better quality of life for postmenopausal women.